Prática de gestão educacional : narrativas de ex-secretários municipais - Margon, Jeferson (2016)
The research on educational organization management in Brazil has been based primarily on the schools, rather, on school management. Differently, this study was directed towards discussing educational systems management, that is, the level of Secretariat